When cultures collide : managing successfully across cultures - Lewis, Richard D. (Richard Donald), 1930- (London ; Naperville, Ill. : Nicholas Brealey, 1999)
This book is about: Getting to grips with cultural diversity; Managing across cultures; Getting to know each other.
Keywords: Business; Management; Enterprises; International business enterprises -- Management; Intercultural communication; Management -- Social aspects